Integration and leadership in Southern Africa: South Africa's strategy, opportunities and limitations - Mamphogoro, Rabelani Daniel (My University, 2018)
After South Africa experienced a political transition in 1994, the regional integration dynamic in southern Africa also went under a considerable change. The new South Africa became a natural member of the Southern African Development Community (SADC), and also adopted the Southern African Customs Union (SACU). South Africa’s accession into SADC and its membership in SACU raised questions about its capability to lead and strengthen regional integration in the southern African region. Also central to this question was the debate around the best institutional framework that South Africa should use to promote regional integration in southern Africa. However, since the 1994 political transformation, South Africa has maintained a neutral policy position and strove to prove its capacity to lead and integrate the southern African region using both SADC and SACU. Thus, South Africa’s policy position has inspired two postures that are evoking that Pretoria should take a decisive policy position that will reflect on the path that it is has chosen to promote regional integration in southern Africa. However, despite the evocations from these two perspectives, South Africa has not yet taken either side of the policy positions on its approach to regional integration in southern Africa. Therefore it is against this background that this study seeks to engage into the argument of these perspectives, however, driven by the main objective of assessing South Africa’s capacity to lead, drive and strengthen southern African regional integration in the post-1994 era.
A research report submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Arts in International Relations, 2017
Keywords: Southern African Development Community; Africa, Southern--Economic integration; South Africa--Economic conditions; South Africa--Politics and government--1994-